The Takete—Maluma Phenomenon in Autism Spectrum Disorders. (February 2013) - Occelli, Valeria; Esposito, Gianluca; Venuti, Paola; Arduino, Giuseppe Maurizio; Zampini, Massimiliano
It has been reported that people tend to preferentially associate phonemes like /m/, /l/, /n/ to curvilinear shapes and phonemes like /t/, /z/, /r/, /k/ to rectilinear shapes. Here we evaluated the performance of children/adolescents with autism spectrum disorders (ASD) and neurotypical controls in this audiovisual congruency phenomenon. Pairs of visual patterns (curvilinear vs rectilinear) were presented to a group of ASD participants (low- or high-functioning) and a group of age-matched neurotypical controls. Participants were asked to associate each item to non-meaningful phoneme clusters. ASD participants showed a lower proportion of expected association responses than the controls. Within the ASD group the performance varied as a function of the severity of the symptomatology. These data suggest that children/adolescents with ASD show, although at different degrees as a function of the severity of the ASD, lower phonetic-iconic congruency response patterns than neurotypical controls, pointing to poorer multisensory integration capabilities.